Hubungan Antara Penguasaan Kosakata Dengan Kemampuan Memahami Cerpen Bahasa Jerman - Nurhidayah Nurhidayah; Ambo Dalle; Syamsu Rijal (Academic : Journal of Social and Educational Studies, 2022)
Abstract. This research was conducted to obtain data and information about the relationship between vocabulary mastery and the ability to understand short stories in German for class XI IPS students of SMA NEGERI 9 SINJAI. The variable in this study is vocabulary mastery (X) with the ability to understand short stories (Y). The population in this research sample is class XI IPS 2 SINJAI and the sample in this study was conducted randomly or Random Sampling, amounting to 28 students of class XI IPS 2 SINJAI. The data from this study were obtained from a vocabulary mastery test with a reading ability test. Based on the results of the product moment correlation data analysis, it shows that the calculated R is greater than the R table (0.737 > 0.374). The results of data analysis showed that there was a significant positive relationship between vocabulary mastery and the ability to understand short stories in German for class XI IPS SMA NEGERI 9 SINJAI.Keywords: Relationship, Vocabulary Mastery, Ability To Understand, Short Stories.